A children's hospice funded team to develop transitional pathways between acorns and adult providers. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Reed, Christopher; Turner, Pat
Abstract : Motivation: Acorns has previously identified through a feasibility study that there is little proactive coordination in respect of planned transition to adult services for our clients. There are circa 110 young adults using Acorns presently facing the prospect of transition to adult care. Problem statement: At a time when many young people are at their most vulnerable Acorns would provide on-going support that would address the future aspirations of every young person we care for, as well as ensuring that their palliative care needs are met. The Transition Team will enable young people to access services for adults through the familiar organisation of Acorns. There would be no abrupt end of services and young people would be enabled to make choices about their future supported by an organisation they know and trust. Approach: The 36 month target to complete transition from Acorns to adult services requires 3 P/T workers and F/T manager to work across the Acorns region. Working alongside existing community workers, preparation for adulthood will take place to enable discharge from the children's service and engagement with the adult sector. This involved liaison/partnership with external 'adult' agencies offering services to life limited young people. Delivery of this service will follow a care model devised from the ACT Transitional Pathway. Conclusion: Life Limited Young people need options and choices for future care. There is a need to empower life limited young people and their families to advocate for themselves. Previous project work carried out by Acorns highlights the need for an appropriately (transition) worker. Life limited young adults with profound physical and learning disabilities need comparable services in the adult sector in order to monitor and maintain health. Health needs are not the only component of transition which requires addressing.